African-Brazilian Health: contribuitions to promote equity - Isabel CF da Cruz (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
Presents research reports that point out the impact of racism and discrimination to the well-being and health of the African-Brazilian people. The contributors, all well qualified and well known in their fields, are also political activists of the negro movement.